2015
DOI: 10.1371/journal.pone.0124918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiac Arrest on Cognitive Impairment and Hippocampal Plasticity in Middle-Aged Rats

Abstract: Cardiopulmonary arrest is a leading cause of death and disability in the United States that usually occurs in the aged population. Cardiac arrest (CA) induces global ischemia, disrupting global cerebral circulation that results in ischemic brain injury and leads to cognitive impairments in survivors. Ischemia-induced neuronal damage in the hippocampus following CA can result in the impairment of cognitive function including spatial memory. In the present study, we used a model of asphyxial CA (ACA) in nine mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 68 publications
2
69
0
Order By: Relevance
“…Additionally, ischemia-induced enhancement of plasticity may be limited further from the infarct 13 . Here, we tested cognition with hippocampal-dependent contextual fear conditioning 7 . Our previous studies find no gross neuronal loss in the hippocampus after focal ischemia 5 and extensive hippocampal neuronal loss after global ischemia 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, ischemia-induced enhancement of plasticity may be limited further from the infarct 13 . Here, we tested cognition with hippocampal-dependent contextual fear conditioning 7 . Our previous studies find no gross neuronal loss in the hippocampus after focal ischemia 5 and extensive hippocampal neuronal loss after global ischemia 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Focal cerebral ischemia was achieved with intraluminal suture blockage of the middle cerebral artery for 90 minutes 5, 6 . Global cerebral ischemia was induced with 8-minute asphyxia cardiac arrest 5, 7 . Physiological parameters were maintained within normal ranges during surgeries (Online Supplement).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cerebral ischemia can impair cognitive functions, e.g. spatial learning and memory, and aggravate Ab-induced cognitive deficiencies (Kiryk et al 2011;Li et al 2011;Cohan et al 2015).…”
Section: Vascular Dysfunction In Admentioning
confidence: 99%
“…Transient ischemic brain injury and Alzheimer's disease (AD) are two known disorders characterized by progressive neurodegeneration, which initially triggers neuronal death in the hippocampus in the CA1 region and then in the CA3 area [1][2][3][4][5], ulti-mately leading to the development of dementia [6][7][8]. It has been observed that post-ischemic dementia is associated with both the progressive loss of pyramidal neurons of the CA1 and CA3 hippocampal areas, as well as its gradual atrophy [3,4,9,10], in the same way as in AD [5,11].…”
Section: Introductionmentioning
confidence: 99%